2013
DOI: 10.1007/s11605-013-2266-6
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Versus Nonsurgical Treatment of Infected Pancreatic Necrosis: More Arguments to Change the Paradigm

Abstract: Initial nonsurgical approach in IPN is associated with better results both in cases which respond to this treatment as well as in those who, failing this conservative approach, have to be operated on after a delayed period. Primary surgically treated patients had a more severe disease at the time of IPN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…The diagnosis of infected necrosis is an absolute indication for antibacterial drugs [86]. Despite the fact that the majority of patients with pancreatic infection require surgical intervention, the available clinical experience suggests that conservative treatment alone with carefully targeted antibacterial therapy will suffice in certain categories of patients [87][88][89][90][91][92]. The choice of antibiotic for infected necrosis is determined by the pathogenic bacterial agent and its sensitivity to antibiotics.…”
Section: Antibacterial and Antifungal Therapy In Patients With Infectmentioning
confidence: 99%
“…The diagnosis of infected necrosis is an absolute indication for antibacterial drugs [86]. Despite the fact that the majority of patients with pancreatic infection require surgical intervention, the available clinical experience suggests that conservative treatment alone with carefully targeted antibacterial therapy will suffice in certain categories of patients [87][88][89][90][91][92]. The choice of antibiotic for infected necrosis is determined by the pathogenic bacterial agent and its sensitivity to antibiotics.…”
Section: Antibacterial and Antifungal Therapy In Patients With Infectmentioning
confidence: 99%
“…However, there are numerous studies evaluating conservative treatment of infected necrosis [16,36,37,38]. A systematic review of 12 studies analyzed a total of 409 patients with infected pancreatic necrosis [16].…”
Section: How Conservative Can We Be?mentioning
confidence: 99%
“…Another analysis of 639 consecutive patients with necrotizing pancreatitis showed that 62% of patients can be treated without intervention and with low mortality [17]. Other authors confirmed the safety and feasibility of conservative treatment of infected pancreatic necrosis as well [36,37,38]. Looking at all the special considerations in these different studies, it is very important to point out that patients with acute necrotizing pancreatitis should be treated in specialized centers only [19,35].…”
Section: How Conservative Can We Be?mentioning
confidence: 99%
“…In the last two decades, significant changes have occurred in the treatment of infected pancreatic necrosis. Namely, surgical intervention has been postponed and minimally invasive techniques have been introduced 4 - 6 .…”
Section: Introductionmentioning
confidence: 99%
“…In some situations, the intervention for drainage may be delayed to the point that the patient recovers completely, and no invasive procedure is required. Various studies have demonstrated that selected patients with infected pancreatic necrosis can be successfully managed exclusively by clinical treatment 4 , 15 - 17 . The objective of this paper is to present our experience in the management of patients with pancreatic necrosis and gas in the retroperitoneum who were treated exclusively with antibiotics and did not require any type of drainage.…”
Section: Introductionmentioning
confidence: 99%